The Students’ Perception of Artificial Intelligence-Based Instruction in Speaking Class - Mujahidah; Kisman Salija; Muhammad Asfah Rahman (ELITE Association Indonesia, 2023)
ABSTRACT Now days, technology in teaching is needed very much. Most of lecturer cannot teach without technology. Including in teaching English. Technology is an effective way to teach English (Cioffy, 2020). Artificial Intelligence (AI) is a technology created by human and can do what the human do, even better than human. So, this study focuses on the students’ perceive of Artificial Intelligence based-instruction in English Language Teaching. This research used a survey method with descriptive analysis. This research involved the students of the English Department who have studied English by using Artificial Intelligence (AI). The populations of this research were English Department students, was taken 100 students as sample. The number of samples is taken by using randomly. This research focus on 4 constructs of studies according to the theory of Technology Acceptance Model (TAM) that develop by Davis in Ayu Mira (2016) with the students’ perception of Easy to use, the Usefulness of AI in English, the students’ attitude, and the students’ behavioural Intention of AI in English. All the data of the construct were taken by using a questionnaire. The result of this study shows that, the students’ acceptance of Artificial Intelligence is very good, whereas, the Students’ Perception of AI Perceived Ease of Use (PEU) is mostly high, and using AI seems easy to operate, use, and access for the students and in the same time the Students’ Perceived Usefulness (PU) of AI is helpful. The data presents sixrteen different statements related to students’ perceived usefulness. The data consists of fourteen items that obtain a high level and two items that indicate a low level. In summary, the use of AI in English will be a positive choice and useful. The top mean score is 4.13 which states that the students found it helpful to use AI products in every study of English. Future more based on the data taken, it depicts that the student's Attitude Toward Using (ATU) of AI is almost varies. They have a good feeling that those people would support them to use AI in the process of learning English. It is proven that the students are unlikely to have a problem recognizing AI in learning English. The highest mean score, 3.93, presents that the use of AI is beneficial to the students. Most students think that AI products have a positive impact for using in learning English. The last about the student's Behavioral Intention (BI) of AI is balanced between the high-level items and the middle-level items with no low-level items. This means the students’ intention toward AI in English is promising. The students intend to use AI products in the future and frequently as well as recommend them to other people to use AI products. The middle-level is all about the purchase of the AI product. It indicates that there is still hesitation to own AI products when it comes to taking money to do it. The highest item proves that AI products will be used in the future with a mean score, of 4.08. It shows how high the students are looking forward to using AI products in the future. Keyword: Artificial Intelligence, Perceive, ELT, Instruction